POLAND’S “FAMILY 500+” PROGRAM AS AN OPPORTUNITY TO SOLVE THE PROBLEMS OF FAMILY AND DEMOGRAPHIC POLICY - Anna Milewska; Daniel Błażejczyk (Polityki Europejskie, Finanse i Marketing, 2020)
The goal of this article was to identify and characterize the socio-economic effects of theintroduction of the “Family 500+” program in Poland. The research part focused on checking theimplementation of the assumptions, which were placed on the introduction of the "Family 500+"program. The main focus of the study was fertility, the improvement of which is a key goal of theprogram.The research methods used in the article were: data analysis method - data on the number ofbirths of children in Poland, the fertility rate as well as the method of synthesis, inference andinterpretation were analyzed. On the basis of the data analysis, conclusions were drawn and theirnature explained. This was done in order to reflect on the effectiveness of public spending on the"Family 500+" program.To achieve the intended objective, research and analysis were carried out using selectedindicators and statistical data. Their results allowed to verify the effectiveness of public fundsspent on the indicated program.